Assessing the viability of drone technology for e-commerce last-mile deliveries: a business case analysis - Schübel, Ramin Leon (2023)
The integration of drone technology in logistic systems is a rapidly growing area of scientific research. This work project reports findings from expert interviews and a survey on the viability of drone technology as a method for last-mile deliveries in the e-commerce industry alongside a comprehensive review of existing academic literature in this domain. Several influencing factors were used to discuss results from a business and customer perspective on an economical, technological, and operational dimension. Overall, the results indicate that drones are not feasible for last-mile e-commerce deliveries, combining infeasibility from a business perspective and feasibility from a customer perspective.